ANTs using alternative and non-traditional investments to allocate your assets in an uncertain world - Froehlich, Robert J.; 1940- 1951- 1953- 1950-; 1950- 1963- (Hoboken, N.J. John Wiley & Sons, 2011)
With the financial crisis and increasing volatility in the markets, views on asset allocation have changed with an increased focus on incorporating non-traditional (stocks and bonds) investments into the average portfolio-- |c Provided by publisher.
Includes index.
Keywords: Investments; Asset allocation; Portfolio management; Finance